Analysis of Student Misconceptions Using the Three-tier Diagnostic Test on Atomic Structure Class X Material at SMA N 1 Lintau Buo - Tustari, Rahma; Herman, Mimi; Sari, Dwivelia Aftika; Mawarnis, Elvy Rahmi; Herman, Hidayat (Universitas Pendidikan Mandalika, 2025)
This research is motivated by the number of students who experience misconceptions so that they are not successful in chemistry subjects. This study aims to determine the misconceptions that occur in class X students at SMA N 1 Lintau Buo using a three-tier diagnostic test on atomic structure material. In this study using a qualitative approach (descriptive) method. The subjects of this study were class X students with a total of 108 people. The instruments used are the main instrument (the researcher himself) and supporting instruments, namely the three-tier diagnostic test, interviews, observation and documentation. Data validity testing was carried out by increasing persistence and data triangulation. Furthermore, the data analysis technique uses the classification of student answers from the three-tier diagnostic test, then a percentage is obtained based on the atomic structure sub-matter which is grouped into categories of conceptual understanding, misconceptions and not conceptual understanding. Based on the research that has been done, it can be concluded that the results of the analysis of student misconceptions using the three-tier diagnostic test on class X atomic structure material at SMA N 1 Lintau Buo “are that there are two sub-matter of atomic structure with misconceptions with high criteria, namely in the sub-matter of atomic notation based on the number of protons, neutrons and electrons by 69% and sub-matter of isotopes, isobars and isotones by 62%. For the overall atomic structure sub-matter, the average in the concept understanding category is 36% medium criteria, the misconception category is 55.6% medium criteria and the category does not understand the concept of 8.4% low criteria.